Unravelling the early photochemical behavior of (8-substituted-7-hydroxyquinolinyl)methyl acetates through electronic structure theory and ultrafast transient absorption spectroscopy. Issue 2 (12th December 2016) - Ma, Jiani; Mewes, Jan-Michael; Harris, Kyle T.; Dore, Timothy M.; Phillips, David Lee; Dreuw, Andreas
Abstract : Role of solvent, prototropic states, excited state proton transfers, and excited states on biological effector release from quinoline-based phototriggers. Abstract : The photophysical processes and photochemical reactions in the ultrafast time region of (8-bromo-7-hydroxyquinolin-2-yl)methyl acetate (BHQ-OAc) in acetonitrile and neutral aqueous solutions were investigated using quantum chemical calculations and femtosecond transient absorption spectroscopy. After initial excitation into the π, π* excited state, BHQ-OAc undergoes an ultrafast intersystem crossing (ISC) into a π, π* excited triplet state on a timescale of 16 ps. The n, π* and π, π* excited singlet and triplet states involved in the photochemistry were identified by means of their characteristic excited state absorption (ESA) bands and from second order coupled-cluster (CC2) calculations. The high ISC rate of BHQ-OAc and related compounds is traced back to involvement of almost energetically degenerate n, π* excited states that enable efficient ISC that obeys El-Sayed's rules.